Faktor-Faktor yang Berpengaruh terhadap Kinerja Usaha Wirausaha Wanita: Suatu Studi pada Industri Pangan Rumahan di Bogor - Sumantri, Bayu; Fariyanti, Anna; Winandi, Ratna (SBM ITB, 2013)
One of the industry many cultivated by women entrepreneurs in Indonesia is home industry. The majority of categories business carried on women entrepreneurs in Bogor is business related food. Many factors influence why business performances which is run by women entrepreneurs are not experiencing progress. This research aims at analyze the correlation personal characteristics with business performance of women entrepreneurs on the home food industry and analyze the factors affecting the performances of business women entrepreneurs on the home food industry. The number of samples taken is 100 women entrepreneurs. Data processed in qualitative and quantitative. Qualitative Data processed with descriptive, whereas quantitative data processed by using Rank Spearman and SEM (Structural Equation Modelling) analysis. This research found that women entrepreneurs on home food industry in Bogor showed that education, training, age, ethnic origin, and family background correlated with income; work experience correlated with selling volume; education, training, age, and work experience correlated with expansion area marketing. Beside that, this research found that business performance is influenced by personal characteristics, entrepreneurship, internal and external environment, where personal characteristics of women entrepreneurs on home food industry in Bogor is the most important variables that affect the business performance of women entrepreneurs. Keywords: women entrepreneurs, personal characteristics, entrepreneurship, business performances, internal and external environment